Evidence for Microbial Mediated NO3− Cycling Within Floodplain Sediments During Groundwater Fluctuations - Bouskill, Nicholas J.; Conrad, Mark E.; Bill, Markus; Brodie, Eoin L.; Cheng, Yiwei; Hobson, Chad; Forbes, Matthew; Casciotti, Karen L.; Williams, Kenneth H. (Frontiers in Earth Science, 2019)
The capillary fringe is a subsurface terrestrial-aquatic interface that can be a significant hotspot for biogeochemical cycling of terrestrially derived organic matter and nutrients. However, pathways of nitrogen (N) cycling within this environment are poorly understood, and observations of temporal fluctuations in nitrate (NO3 ) concentrations lack the necessary resolution to partition between biotic or abiotic mechanisms. At discrete sampling points we measured NO3 , nitrite (NO2 ), ammonium (NH4 +), gaseous nitrous oxide (N2O) and nitrogen (N2), and the corresponding isotopic composition of NO3 within floodplain sediments at Rifle, Colorado. Coincident with an annually reoccurring spring/ summer excursion in groundwater elevation driven by snowmelt, we observed a rapid decline in NO3 followed by transient peaks in NO2 , at three depths (2, 2.5 and 3 m) below the ground surface. Isotopic measurements (15N and 18O of NO3 ) suggest an immediate onset of biological N loss at 2 m. At 2.5 and 3 m, NO3 concentrations declined initially with no observable isotopic response, indicating dilution of NO3 as the NO3 -deficient groundwater rose, followed by denitrification after prolonged saturation. A simple Rayleigh model further supports this depth-dependent variability in the significance of actively fractionating mechanisms (i.e., NO3 reduction) relative to non-fractionating mechanisms (mixing and dilution). NO3 reduction was calculated to be responsible for 64 % of the NO3 decline at 2 m, 28 % at 2.5 and 47 % at 3 m, respectively. Finally, by accounting for previous molecular and geochemical analysis at this site, and comparing the trajectories between 15N: 18O, we conclude that biological NO3 consumption at the two deeper and frequently saturated depths (2.5 and 3 m) can be attributed to heterotrophic denitrification. However, the 15N: 18O trajectory at the shallower, irregularly saturated site at 2 m shows a more complicated relationship best explained by the cyclic production of NO3 via aerobic oxidation, and consumption via NO3 reduction.